PENDIDIKAN ISLAM, PENDIDIKAN POLITIK, DAN DIALOG ANTAR UMAT BERAGAMA DI INDONESIA - Masamah, Ulfa (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2016)
Islamic education generates sufficient intellectual abilities muslim political culture that gave birth to the humanistic-theocentric, humanistic-patriotic, and if they fail to cultivate the intellect will give birth to a political culture that hedonistic-egoistic. Seeing the current political conditions, the reconstruction of political education to strengthen the social contract-religious dimension in Islamic education is very urgent to be held. Repair religious education aims to crystallize the mono-religious experience of being an open attitude that is important to prepare future generations for public order dialogue. Political education requires the democratization of space as a means to build a society of dialogue with the orientation changes in behavior and attitudes, the quality and variety of aspects. Political education is oriented to instill democratic values such as openness, mutual respect, sympathy, empathy, solidarity, and their understanding of pluralism in Indonesia is a pluralistic community life. That the concept of moderation which avoids extremes in the two sides, in order to create al-ummatan wasathan. Order harmonious religious life based on religious values will be realized through dialogue faiths. Inter-religious dialogue as a vehicle find the idea of a progressive and avoid manipulative ways and aggressiveness of religious communities. It should, dialogue functioned as the main way to build mutual understanding religious communities. Routines dialogue conducted by government agencies, social institutions, and religious leaders must be improved. This is because the results of the next dialog will apllicate in religious life, nation, and state in Indonesia.